Examining the Supply Chain Impact on Labor Social Security in Indonesia: A Systems Thinking Analysis - Nova Novita; Ficky Alkarim; Irwanda Wisnu Wardhana; Poempida Hidayatullah (International Journal of Supply Chain Management, 2020)
Abstract—Supply chains, production networks and other complex inter-organisational relationships are defining features of contemporary business organisations. This article reviews the impact of supply chain pressures on work, employment relations and human resource management, with a particular emphasis on domestic-oriented supply chains. By utilizing systems thinking, we identify and translate several variables into the Causal Loop Diagram (CLD) to clarify the linkages among them. We found seven determinants that have contributed to the low level of labor social security membership namely: competition, lack of insurance minded, ineffective communication, incompetent marketing agents, dis-harmonized regulations, weak law enforcement, and unattractive incentives for marketing agents. This paper could benefit supply chain to evaluate the existing membership program and to improve its quality and approach. Moreover, policymakers could utilize findings and recommendations from this study to perfecting the policy based on evidence.